Inovasi dalam Manajemen Sumber Daya Pendidikan Islamuntuk Menjawab Tantangan Globalisasi - Dwi Arini; Musyarapah Musyarapah (Jurnal Teologi Islam, 2026)
Islamic education in Indonesia faces increasingly complex challenges of globalization, including technological disruption, global human resource competition, and demands for the integration of Islamic values ​​with scientific advancements. This paper examines innovations in Islamic education resource management (SDPI) as an adaptive strategy to address these dynamics. Through a qualitative literature study approach with thematic content analysis, this study identifies SDPI management innovation concepts based on the maqasid sharia and digital transformation. The results indicate that key innovations include human resource development through technology-based continuous professional development, an integrative curriculum that eliminates the dichotomy between religious and general knowledge, and optimization of digital infrastructure. In the Indonesian context, particularly in Central Kalimantan, infrastructure challenges and the digital divide remain dominant, despite an increase in madrasah student access reaching 93,078 by 2025. The proposed innovation includes the “SIEM-MaqaTech” (Sustainable Islamic Education Management based on Maqasid and Technology) model that integrates spiritual values, 21st-century competencies, and multi-stakeholder collaboration. This research contributes controversially by enriching the contemporary Islamic education management framework and providing practical policy recommendations for madrasah administrators and local governments. Thus, Islamic education can remain relevant, competitive, and characterized by rahmatan lil 'alamin (blessing for the universe) in the era of globalization.